Dosimetry auditing procedure with alanine dosimeters for light ion beam therapy - Ableitinger, Alexander; Vatnitsky, Stanislav; Herrmann, Rochus; Bassler, Niels; Palmans, Hugo; Sharpe, Peter; Ecker, Swantje; Chaudhri, Naved Sarwar; Jäkel, Oliver; Georg, Dietmar (Radiotherapy and oncology, 2013)
Background and purpose - In the next few years the number of facilities providing ion beam therapy with scanning beams will increase. An auditing process based on an end-to-end test (including CT imaging, planning and dose delivery) could help new ion therapy centres to validate their entire logistic chain of radiation delivery. An end-to-end procedure was designed and tested in both scanned proton and carbon ion beams, which may also serve as a dosimetric credentialing procedure for clinical trials in the future. The developed procedure is focused only on physical dose delivery and the validation of the biological dose is out of scope of the current work. - Materials and methods - The audit procedure was based on a homogeneous phantom that mimics the dimension of a head (20×20×21cm3). The phantom can be loaded either with an ionisation chamber or 20 alanine dosimeters plus 2 radiochromic EBT films. Dose verification aimed at measuring a dose of 10Gy homogeneously delivered to a virtual-target volume of 8×8×12cm3. In order to interpret the readout of the irradiated alanine dosimeters additional Monte Carlo simulations were performed to calculate the energy dependent detector response of the particle fluence in the alanine detector. A pilot run was performed with protons and carbon ions at the Heidelberg Ion Therapy facility (HIT). - Results - The mean difference of the absolute physical dose measured with the alanine dosimeters compared with the expected dose from the treatment planning system was −2.4±0.9% (1σ) for protons and −2.2±1.1% (1σ) for carbon ions. The measurements performed with the ionisation chamber indicate this slight underdosage with a dose difference of −1.7% for protons and −1.0% for carbon ions. The profiles measured by radiochromic films showed an acceptable homogeneity of about 3%. - Conclusions - Alanine dosimeters are suitable detectors for dosimetry audits in ion beam therapy and the presented end-to-end test is feasible. If further studies show similar results, this dosimetric audit could be implemented as a credentialing procedure for clinical proton and carbon beam delivery.